Pengolahan Plastik Bekas Menjadi Bantal Hias Di Desa Ngempit Kecamatan Kraton Kabupaten Pasuruan - Sholihah, Fitri Awaliyatush; Normaladewi, Andi; Laksono, Prayitno Tri (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Plastic waste that can threaten the environment is increasingly overflowing in many areas. Therefore, this program is aimed to utilize waste banks by processing plastic waste into decorative pillows in Ngempit village, Kraton, Pasuruan in collaboration with the Community Information Group Surya Harapan and Etza Accesories. This program not only save the environment, but it also produces decorative pillow products which can also be a feature product of the village, so that this program indirectly can develop the creative economy of the people in Ngempit village. The method applied in this partnership program is counseling, training, demonstration and assistance. The results of the community partnership program are counseling and training on processing plastic waste into decorative pillows, counseling on marketing strategies, counseling on determination of selling price, as well as demonstration or practice of producing decorative pillow made from plastic waste with special designs, which are pictures and words in English. Finally, as a starting point, the product has been marketed at Surya Madani Business Enterprise in Ngempit village